2018
DOI: 10.1590/0001-3765201820180072
|View full text |Cite
|
Sign up to set email alerts
|

Grafting height does not affect Fusarium wilt control or horticultural performance of Passiflora gibertii N.E.Br. rootstock

Abstract: The influence of the grafting height (5, 10, 20 and 30 cm above the root collar) of P. edulis on P. gibertii was evaluated on the incidence of Fusarium wilt and horticultural performance. Plants of P. gibertii grafted on P. edulis and non-grafted plants of both species were also studied. In addition, histopathological studies were also performed on the roots of non-grafted P. edulis collected at three severity stages of Fusarium wilt. In greenhouse, the graft take was inversely related to the grafting height i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In passion fruit (Passiflora gibertii N.E.Br. ), for example, grafting height was effective in increasing vigor in nursery conditions (Lima et al, 2018). In the present study, a reduction in graft survival was observed as the height of the grafting point increased, which does not seem to be related to vascularity since the morphological patterns of the grafts in the 110 and 280-cm 3 containers were similar.…”
supporting
confidence: 47%
“…In passion fruit (Passiflora gibertii N.E.Br. ), for example, grafting height was effective in increasing vigor in nursery conditions (Lima et al, 2018). In the present study, a reduction in graft survival was observed as the height of the grafting point increased, which does not seem to be related to vascularity since the morphological patterns of the grafts in the 110 and 280-cm 3 containers were similar.…”
supporting
confidence: 47%
“…Among the diseases caused by soil pathogens, Fusarium wilt, caused by the fungus Fusarium oxysporum f. sp. passiflorae (FOP), has major impact on passion fruit culture since there is no effective means of control or management strategies (Lima et al 2018(Lima et al , 2019Melo et al 2019;Pereira et al 2019). Disease control is complex since the pathogen survives for a long period in the soil as chlamydospores (Bennett and Davis 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An inefficient selection can compromise all the other phases and furthermore, the entire breeding program. Selection in the field has followed the traditional in-use method (Pereira et al 2019); however, it is time consuming, costly and can be influenced by soil patterns and heterogeneity in pathogen distribution (Lima et al 2018;Pereira et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic breeding programs of sour passion fruit (Passiflora edulis Sims) aims to obtain genotypes with high productive potential and fruit quality, such as high juice yield and content of soluble solids and low acidity. In addition, resistance is necessary to the main pathogens that shorten the lifespan of orchards in different regions of Brazil (Lima et al 2018;Pereira et al 2019;Santos et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the genotypic observations according to the initial harvests can accelerate the selection process and consequently reduce the cost of breeding programs. This acceleration is particularly interesting for the selection of yellow passion fruit, since the lifespan of the crop is declining due to the high incidence and severity of diseases (Oliveira et al 2013;Lima et al 2018;Pereira et al 2019). Under ideal conditions, the culture is maintained commercially for up to four years, but this falls to one year in the presence of diseases caused by viruses and fungi, such as fusarium wilt (Oliveira et al 2013;Pereira et al 2019).…”
Section: Introductionmentioning
confidence: 99%